2006
DOI: 10.1051/0004-6361:20065410
|View full text |Cite
|
Sign up to set email alerts
|

An asymmetry detected in the disk of κ Canis Majoris with AMBER/VLTI

Abstract: Aims. We study the geometry and kinematics of the circumstellar environment of the Be star κ CMa in the Brγ emission line and its nearby continuum. Methods. We use the AMBER/VLTI instrument operating in the K band, which provides a spatial resolution of about 6 mas with a spectral resolution of 1500, to study the kinematics within the disk and to infer its rotation law. To obtain more kinematical constraints we also use a high spectral resolution Paβ line profile obtain in December 2005 at the Observatorio do … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 31 publications
(55 reference statements)
3
34
0
Order By: Relevance
“…400 ± 20 km s −1 (compared to 386 ± 21 km s −1 ), but β = −0.35 ± 0.50 This would imply that the disk is rotating faster than Keplerian motion requires. Such a rotational exponent β in the rotation law (7) has already been obtained by Meilland et al (2007a) for the Be star κ CMa, but κ CMa was rotating at only 52% of its critical velocity. However, we have to keep in mind that our simple geometrically thin model might not be fully suitable for stars seen under high inclinations.…”
Section: Disk Kinematics and Starssupporting
confidence: 61%
See 1 more Smart Citation
“…400 ± 20 km s −1 (compared to 386 ± 21 km s −1 ), but β = −0.35 ± 0.50 This would imply that the disk is rotating faster than Keplerian motion requires. Such a rotational exponent β in the rotation law (7) has already been obtained by Meilland et al (2007a) for the Be star κ CMa, but κ CMa was rotating at only 52% of its critical velocity. However, we have to keep in mind that our simple geometrically thin model might not be fully suitable for stars seen under high inclinations.…”
Section: Disk Kinematics and Starssupporting
confidence: 61%
“…These two outstanding characteristics define what is called the "Be phenomenon". The geometry and structure of the envelopes around Be stars have been intensively studied, and there is clear evidence that these environments are axisymmetric and flattened (Dougherty & Taylor 1992;Hanuschik 1996;Quirrenbach et al 1997;Stee 2003;Kervella & Domiciano de Souza 2006;Tycner et al 2008) with a very low expansion velocity (Poeckert & Marlborough 1978b,a;Waters 1986;Waters et al 1987;Waters & Marlborough 1992;Meilland et al 2007a). Studies of accretion disks show that disks in hydrodynamic equilibrium and in Keplerian rotation should be very thin, assuming that their vertical scale height is governed by gas pressure alone.…”
Section: Introductionmentioning
confidence: 99%
“…From CHARA/VEGA measurement to be published in Mourard et al (2014). Stee et al 2012 or radiative transfer codes such as SIMECA (Meilland et al 2007a, Meilland et al 2007b, BEDSIK (Tycner et al 2011), or HDUST (Štefl et al 2009). In all cases the authors found that the circumstellar emission stems from a thin equatorial disk.…”
Section: Mass Loss and Circumstellar Environmentsmentioning
confidence: 99%
“…This case requires a fine-tunning mechanism such that the centrifugal force, v 328 A. C. Carciofi Porter & Rivinius (2003) reviewed the then existing observational constraints on the disc kinematics and concluded that "all of the kinematic evidence seems to point to a disc velocity field dominated by rotation, with little or no radial flow, at least in the regions where the kinematic signatures of emission and absorption are significant". Today, spectrointerferometry and spectroastrometry provides clear-cut evidence that, in most systems observed and analysed so far (κ CMa being the only possible exception, Meilland et al 2007b), the discs rotate in a Keplerian fashion (Meilland et al 2007b, Stefl et al, these proceedings, Oudmaijer et al, these proceedings). This is an important result, seeing that it indicates that viscosity is the driving mechanism of the outflow.…”
Section: Disc Dynamicsmentioning
confidence: 99%